Ultrasound characterization of superficial lymph nodes in HIV patients with Talaromyces marneffei infection - Pan, Lin; Shao, Huaguo (Frontiers in Medicine, 2023)
Abstract Objectives This study aimed at exploring the ultrasound characteristics of superficial lymph nodes (LNs) in HIV patients with Talaromycosis marneffei infection to provide help and understanding for diagnosis and therapy. Methods A retrospective analysis was conducted on 26 patients with confirmed HIV and T. marneffei co-infection, who underwent ultrasound examination and ultrasound guided puncture biopsy at our hospital from March 2015 to March 2023. Results In 26 patients, all patient had lymphadenectasis. LNs of 21 cases (80.76%) showed diffusely hyperechoic with a tulle-like change, including six cases (23.07%) with liquefaction. When the hila were present or thinned, the blood flow signals were primarily hilar, rich or poor, and when the hila were absent, the blood flow signals were peripheral or poor. Axillary LN long diameter to short diameter (L/S)ratios had positive correlation significantly with CD4+T cell counts (r=0.8214, P=0.0341). Patients had retroperitoneal lymphadenectasis had decreased NK cell counts (P=0.0079). Conclusions In summary, T. marneffei infection of LNs in HIV patients is often presenting with superficial LNs enlargement, mostly involving the cervical LNs. The T. marneffei infected LNs have several characteristics in echogenicity, hilum and blood flow signal. And it might be associations between lymphocyte subsets and enlarged superficial LNs. Ultrasound examination should be paid attention if patients have superficial LNs enlargement and diagnosis of T. marneffei infection is considered.